Adaptation, Censorship, and Audiences of Questionable Type: Lesbian Sightings in "Rebecca" (1940) and "The Uninvited" (1944) - Berenstein, Rhona J. (Cinema journal, 1998)
This article analyzes the intertextual relationship between "Rebecca" and "The Uninvited," highlighting the "ghosting" of lesbianism in the act of representation and addressing the mediating role of censorship vis--vis sex perversion.